Bibliometric Analysis of ESD Research in Mathematics Education and Students’ Mathematical Abilities - Sevilla Tita Azzahra; Lilis Marina Angraini (Gema Cendekia Institute, 2026)
This study aims to analyze the trend of scientific publications regarding the application of Education for Sustainable Development (ESD) in mathematics learning to students' mathematical abilities in the 2020–2025 period. The method used is bibliometric analysis by utilizing article data from Google Scholar through Harzing's Publish or Perish (PoP) and analyzed using VOSviewer software. A total of 991 articles were analyzed to examine the development of publications, citation patterns, and the relevance of research themes. The results showed a significant increase in the number of publications, with a total of 9,304 citations and an h-index value of 46. The focus of research shifted to the topics of mathematical problem-solving, creative thinking skills, STEM integration, and the implementation of ESD-based curriculum. However, the theme of the effectiveness of the application of ESD on students' mathematical abilities directly is still relatively limited. This research is important because there have not been many studies that systematically map the direction, dominant focus, and gaps of ESD research in mathematics learning, so that it has the potential to hinder the development of sustainable and targeted research. The impact of this research is to provide a strategic reference basis for researchers and educators in developing advanced research and ESD-based mathematics learning innovations that are relevant and have an impact on strengthening students' mathematical abilities